2007
DOI: 10.1093/jn/137.3.601
|View full text |Cite
|
Sign up to set email alerts
|

Parenterally Fed Neonatal Piglets Have a Low Rate of Endogenous Arginine Synthesis from Circulating Proline

Abstract: Parenterally fed neonatal piglets cannot synthesize sufficient arginine to maintain arginine status, presumably due to the intestinal atrophy that occurs with parenteral feeding. Parenteral feeding-induced atrophy can be reduced by the infusion of glucagon-like peptide 2 (GLP-2). GLP-2 infusion was hypothesized to increase the rate of endogenous arginine synthesis from proline, the major arginine precursor, in parenterally fed piglets receiving an arginine-deficient diet. Male piglets, ) from proline (11.6 vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…In the present communication, we have demonstrated that dietary and plasma proline are in fact the main precursors for citrulline synthesis in the neonatal piglet during fasting and fed conditions. Interestingly, it has been shown that enteral proline is a better precursor than arterial proline (3,32), which we have also confirmed in this report. The contribution of the different enteral amino acids to the rate of appearance of ornithine indicates that not only arginase is absent in the neonatal gut but that proline was the main substrate for enteral OAT.…”
Section: Citrulline Precursorssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present communication, we have demonstrated that dietary and plasma proline are in fact the main precursors for citrulline synthesis in the neonatal piglet during fasting and fed conditions. Interestingly, it has been shown that enteral proline is a better precursor than arterial proline (3,32), which we have also confirmed in this report. The contribution of the different enteral amino acids to the rate of appearance of ornithine indicates that not only arginase is absent in the neonatal gut but that proline was the main substrate for enteral OAT.…”
Section: Citrulline Precursorssupporting
confidence: 91%
“…The rate of appearance of arginine was within the wide range published (32,34,35); the first-pass extraction measured in the current communication (12%), however, was lower than the 50% reported by others (35). Urschel et al (35) reported no changes in first splanchnic extraction despite a ninefold difference in arginine intake, which is surprising because the liver is the main site for (excess) arginine disposal (27).…”
Section: Rate Of Amino Acid Appearance and Conversionsupporting
confidence: 51%
“…1c), the excess proline might be a precursor for arginine synthesis thereby decreasing the efficiency of labeling by the isotope-coded arginine provided. Although proline is known to be one of the main substrates in the formation of citrulline, a direct precursor for arginine biosynthesis, it has been demonstrated that this process is only favorable when there is a lack of available arginine (24,25). Moreover, to date, the presence of other citrulline precursors, such as glutamine in standard SILAC media, has had no reported detrimental effect on SILAC procedures.…”
Section: Resultsmentioning
confidence: 99%
“…However it has been clearly demonstrated in a number of studies that the de novo biosynthesis of either arginine or proline using the other as a precursor is most strongly influenced by their bioavailability (24,25,27). In other words, if there is sufficient free proline present to maintain cellular homeostasis the endogenous production of proline will not be favored, regardless of the concentration of its available precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the conversion of citrulline to arginine is the best measure of total endogenous arginine synthesis, and this method has been successfully used to measure whole body arginine synthesis in adult humans (9). In previous studies, we used the proline-to-arginine conversion as a measure of whole body arginine synthesis in neonatal piglets (27)(28)(29)31); however, how much of the total endogenous arginine synthesis in piglets that arises from proline is currently unknown. By comparing the rate of conversion of proline to arginine to the rate of the citrulline-to-arginine conversion, the relative importance of proline as an arginine precursor can be assessed.…”
mentioning
confidence: 99%